Revealing fantasy consumption on social media, how women read romantic novel on Wattpad app - Pratiwi, Fatma Dian (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
This article aims to reveal how fantasy is consumed on social media, in the context of this research, Wattpad. That is an application that specializes in producing and consuming works of fiction in the form of novels and short stories. This research has a qualitative paradigm and collects data using in-depth interviews and documentation. Novel reading din this research, entitled The Mischievous Mrs. Maxfield, a novel with romantic genre, is then analyzed from the perspective of Psychoanalysis using Fantasy theory. There were two women who were resource persons and had different characters and backgrounds. From the research conducted, it was concluded that the fulfilment of fantasy was not fully carried out by informant X and Y, because according to them, there were other novels that could better fulfil their fantasies than this novel. In addition, the two informants felt that the theme raised in this novel was too exaggerated because it involved the forced marriage of women who were still underage.